A Model for Estimating the Impact of Orthophosphate on Copper in Water. Issue 10 (21st August 2018) - Lytle, Darren A.; Schock, Michael R.; Leo, Jordan; Barnes, Benjamin
Abstract : The nature of copper phosphate minerals in drinking water distribution systems has remained largely unsolved despite being an important link to reducing cuprosolvency. Chemical equilibrium modeling has also largely failed to accurately predict soluble copper in the presence of orthophosphate. The objective of this work was to develop and validate an empirical copper solubility model that considered pH, dissolved inorganic carbon (DIC), and orthophosphate from a series of bench‐scale copper precipitation experiments. An empirical model was constructed that allows for the determination of copper levels in a system given pH, DIC, and orthophosphate data. The predictive reliability of this model was assessed by evaluating a collection of cuprosolvency data from two decades of research and field observations and water treatment reports. The tests yielded a firm correlation between predicted and observed copper levels attested by a regression coefficient of 0.86 for a total of 851 observations.